THE REGULARITY OF INFLUENCE OF TRAFFIC PARAMETERS ON THE PROBABILITY OF REALISATION OF PLANNED PASSENGER TRANSFER AT TRANSFER NODES - Samchuk, G.; Самчук, А. А.; Самчук, Г. О. (Харьковский национальный автомобильно-дорожный университет, 2017)
The article deals with the definition of traffic parameters that ensure the minimum value of the transfer waiting time for passengers. On the basis of experimental studies results, a regression equation to determine the probability of realisation of the planned transfer between a pair of vehicles was proposed. Using the identified regression equation, the transfer waiting time can be assessed for any headway exceeding 7,5 min.
ЗАКОНОМЕРНОСТЬ ВЛИЯНИЯ ПАРАМЕТРОВ ДВИЖЕНИЯ ТРАНСПОРТНЫХ СРЕДСТВ НА ВЕРОЯТНОСТЬ ОСУЩЕСТВЛЕНИЯ ЗАПЛАНИРОВАННОЙ ПЕРЕСАДКИ ПАССАЖИРОВ В ТРАНСПОРТНО-ПЕРЕСАДОЧНЫХ УЗЛАХ
ЗАКОНОМІРНІСТЬ ВПЛИВУ ПАРАМЕТРІВ РУХУ ТРАНСПОРТНИХ ЗАСОБІВ НА ЙМОВІРНІСТЬ ЗДІЙСНЕННЯ ЗАПЛАНОВАНОЇ ПЕРЕСАДКИ ПАСАЖИРІВ У ТРАНСПОРТНО-ПЕРЕСАДОЧНИХ ВУЗЛАХ
Keywords: waiting time; transfer node; probability; simulation experiment; regression equation; arrival time; departure time; время ожидания; транспортно-пересадочный узел; вероятность; имитационный эксперимент; уравнение регрессии; час очікування; транспортно-пересадочний вузол; ймовірність; імітаційний експеримент; рівняння регресії; 656.025.2=111